7 alpha-Hydroxy-beta-Sitosterol from Chisocheton tomentosus Induces Apoptosis via Dysregulation of Cellular Bax/Bcl-2 Ratio and Cell Cycle Arrest by Downregulating ERK1/2 Activation - Tasyriq, Mohammad; Najmuldeen, Ibrahim A.; In, Lionel L.A.; Mohamad, Khalit; Awang, Khalijah; Nagoor, Noor Hasima (Hindawi, 2012)
In continuation of our interest towards the elucidation of apoptotic pathways of cytotoxic phytocompounds, we have embarked upon a study on the anticancer effects of 7 alpha-hydroxy-beta-sitosterol (CT1), a rare natural phytosterol oxide isolated from Chisocheton tomentosus. CT1 was found to be cytotoxic on three different human tumor cell lines with minimal effects on normal cell controls, where cell viability levels were maintained >= 80 upon treatment. Our results showed that cell death in MCF-7 breast tumor cells was achieved through the induction of apoptosis via downregulation of the ERK1/2 signaling pathway. CT1 was also found to increase proapoptotic Bax protein levels, while decreasing anti-apoptotic Bcl-2 protein levels, suggesting the involvement of the intrinsic pathway. Reduced levels of initiator procaspase-9 and executioner procaspase-3 were also observed following CT1 exposure, confirming the involvement of cytochrome c-mediated apoptosis via the mitochondrial pathway. These results demonstrated the cytotoxic and apoptotic ability of 7 alpha-hydroxy-beta-sitosterol and suggest its potential anti-cancer use particularly on breast adenocarcinoma cells.